Pelatihan Penyusunan Anggaran Kampung Bagi Aparatur Kantor Pemerintahan Kampung Asei Kecil Di Kabupaten Jayapura - Asnawi, Meinarni; Sesa, Pascalina V.S.; Lamba, Ramasoyan Arung (The Community Engagement Journal, 2023)
Every development in the village/village requires a lot of money. According to Law No. 6 of 2014, village funds are funds sourced from the Revenue and Expenditure Budget (APBN) intended for villages that are transferred through the district/city Regional Revenue and Expenditure Budget (APBD) and used to finance governance, implementation, development, community development, and community empowerment. According to Indonesia Corruption Watch (ICW), corruption cases in the village budget sector were the most cases, there were 46 corruption cases in the village budget sector out of 271 corruption cases in 2019. Village budget corruption was recorded to give state losses of up to Rp. 32.3 billion. Village’s Revenue and Expenditure Budget is an annual financial plan of the village government approved by the Village Consultative Body (Bamuskam). Village Revenue and Expenditure Budget (APB Kampung) consist of Village Revenue, Village Expenditure, and Village Financing which are presented in accordance with the Village APB format in accordance with Permendagri 113 of 2014. Village Budgeting Training for the Apparatus of the Asei Kecil Village Government Office in Jayapura Regency uses an experimental method using a practical method of identifying and compiling a village budget and a direct confirmation method in the form of simple questions related to the importance of village financial management in encouraging the welfare of the village community. Keywords: Village’s Revenue and Expenditure Budget, The welfare of the village community